2006
DOI: 10.1044/1092-4388(2006/032)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Facemask Use on Respiratory Patterns of Women in Speech and Singing

Abstract: The results confirm earlier studies that the vented pneumotachograph facemask does not affect breathing behavior in speech research studies and extends the finding to the study of breathing behavior in singing and to the use of a standard respiratory facemask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In the current study, strong agreement was observed in respiratory kinematics between singing tasks performed with and without a facemask. This demonstrates reliability of the experimental set up and repeatability of the breathing strategies used by both groups [ 30 , 31 , 46 ]. It should be noted that intra-subject repeatability of breathing patterns was not limited to rhythm-related constraints to the duration of inspiration and phonation phases that has been previously reported [ 23 , 46 ], but was also observed for the dynamics of respiratory kinematics (e.g.…”
Section: Resultsmentioning
confidence: 77%
“…In the current study, strong agreement was observed in respiratory kinematics between singing tasks performed with and without a facemask. This demonstrates reliability of the experimental set up and repeatability of the breathing strategies used by both groups [ 30 , 31 , 46 ]. It should be noted that intra-subject repeatability of breathing patterns was not limited to rhythm-related constraints to the duration of inspiration and phonation phases that has been previously reported [ 23 , 46 ], but was also observed for the dynamics of respiratory kinematics (e.g.…”
Section: Resultsmentioning
confidence: 77%
“…Expiratory and inspiratory airflows during the speaking tasks were recorded using a pneumotachograph (airflow) transducer (Biopac SS11lA) that was coupled to the facemask. Previous research has demonstrated that facemasks do not significantly alter breathing patterns (Collyer, Davis, Collyer, & Davis, 2006). Although respiratory activity may be affected by the participants’ use of facemasks in combination with the hand and arm muscle forces needed to hold the mask tightly against the face, participants in the current study were talking comfortably.…”
Section: Methodsmentioning
confidence: 99%
“…Expiratory and inspiratory flows during the speaking tasks were recorded using a pneumotach (airflow) transducer (Biopac SS11lA) that was coupled to the face mask. The use of the face mask was judged acceptable because a prior investigation suggested that face masks do not significantly alter breathing patterns (Collyer & Davis, 2006). However, it must be acknowledged that respiratory activity may have been affected by the use of face masks, as well as by the use of hand and arm muscle force to hold the mask tightly against the face.…”
Section: Methodsmentioning
confidence: 99%